Anti-inflammation effects of Sardinella longicep oil against paw oedema on Rattus novergicus induced by 1% carrageenan - Rima Parwati Sari; Yenny Sugiharto (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: People usually used non steroid anti-inflammation drugs (NSAID) such as aspirin in chronic inflammation treatment. However, using NSAID at long term therapy will cause many effects such as nausea and vomiting. Sardinella longiceps oil, on the other side, is reported as an alternative treatment for anti-inflammation since it is natural and also contained eicosapentaenoid acid (EPA) and decohexaenoic acid (DHA). Thus, it may reduce paw oedema. Purpose: The aim of this study was to know anti-inflammation effects of Sardinella longiceps oil against paw oedema of Wistar rats induced by 1% carrageenan. Methods: The samples of this research were 32 Wistar rats which were divided into four groups, in group 1, the rats were given aquadest; in group 2, the rats were given aspirin; in group 3, the rats were given 1 ml Sardinella longiceps oil; in group 4, the rats were given 1.5 ml Sardinella longiceps oil. All of the rats, nevertheless, were given intraplantar induction of 1% carrageenan into the paw of rats to induce the inflammation condition. Results: All data were tested with normality test. The normal data were then analyzed with Homogenity of Variances and also ANOVA test which result showed significant differences. The data which showed significant differences were tested again with LSD test. result then showed that group given 1 ml Sardinella longiceps oil and group given 1.5 ml Sardinella longiceps oil had no significant differences from group given aspirin, but there were significant differences between group given 1 ml Sardinella longiceps oil and group given 1.5 ml Sardinella longiceps oil, and also between group given 1.5 ml Sardinella longiceps oil and group given aquadest. Conclusion: Sardinella longiceps oil could reduce paw oedema in Wistar rats induced with 1% carrageenan.Latar belakang: Penggunaan obat anti-inflamasi non steroid (OAINS) seperti aspirin sering digunakan dalam pengobatan inflamasi kronis. Namun penggunaan OAINS dalam jangka waktu panjang akan menyebabkan efek samping seperti mual dan muntah. Di sisi lain, minyak Sardinella longiceps, dilaporkan dapat digunakan sebagai alternatif anti-inflamasi karena selain alami, juga terdapat kandungan eicosapentaenoid acid (EPA) and decohexaenoic acid (DHA) yang dapat mengurangi edema pada telapak kaki. Tujuan: Tujuan dari penelitian ini adalah mengetahui efek anti-inflamasi minyak Sardinella longiceps pada edema telapak kaki tikus Wistar yang diinduksi karagenan 1%. Metode: Sampel penelitian ini adalah 32 tikus yang dibagi ke dalam empat kelompok. Kelompok 1, tikus diberi akuades; kelompok 2, tikus diberi aspirin; kelompok 3, tikus diberi minyak Sardinella longiceps 1 ml; kelompok 4, tikus diberi minyak Sardinella longiceps 1,5 ml. Semua tikus tidak terkecuali, diinduksi intraplantar karagenan 1% secara intraplantar pada telapak kaki untuk membuat kondisi inflamasi. Hasil: Semua data dilakukan uji normalitas. Selanjutnya data yang berdistribusi normal dilakukan uji homogenitas dan juga uji ANOVA yanng hasilnya menunjukkan adanya perbedaan bermakna. Data yang menunjukkan perbedaan bermakna diuji lagi dengan LSD. Pada uji LSD menunjukkan bahwa tidak ada perbedaan bermakna antara kelompok minyak Sardinella longiceps 1 ml dengan kelompok aspirin dan kelompok minyak Sardinella longiceps 1,5 ml dengan kelompok aspirin, tetapi ada perbedaan bermakna antara kelompok minyak Sardinella longiceps 1 ml dan kelompok akuades dengan kelompok minyak Sardinella longiceps 1.5 ml group given aquadest. Kesimpulan: Sardinella longiceps dapat mengurangi edema pada telapak kaki tikus Wistar yang diinduksi karagenan 1%.